Cross-Cultural Literacy in Social, Economy and Politic Perspective of Studies TISOL - Alpan Ahmadi (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
This research aims to 1) describes cross-cultural literacy on the people of the world;2) describes the relationship among the socio-culture with social, economy andpolitic; 3) describe the TISOLlearning to the world community on the socio-economic and politic landscape. This research uses a review of the literature and observation on foreign learners studying in Indonesia. The results of this study indicate the existence of a positive relationship between socio-culture literacy and Indonesia with social, economic and Indonesian political to the world community. Therefore, in this research are expected the presence of law strength to keep the learners of Indonesian is not mastered all aspects of life that existed in Indonesia. Penelitian ini bertujuan untuk 1) mendeskripsikan literasi lintas budaya pada masyarakat dunia; 2) mendeskripsikan hubungan antara budaya dengan sosial, ekonomi, dan politik, 3) mendeskripsikan pembelajaran BIPA pada masyarakat dunia dalam tataran sosial, ekonomi, dan politik. Penelitian ini menggunakan tinjauan pustaka dan observasi pada pembelajar asing yang belajar di Indonesia. Hasil penelitian ini menunjukan adanya hubungan positif antara litetasi budaya dan bahasa Indonesia dengan sosial, ekonomi, dan politik Indonesia terhadap masyarakat dunia. Oleh karena itu dalam penelitian ini diharapkan adanya kekuatan hukum untuk menjaga agar masyarakat yang belajar bahasa Indonesia tidak menguasai segala aspek kehidupan yang terdapat di Indonesia. Kata kunci: literasi lintas budaya, sosial ekonomi dan politik, BIPA